Letters to the Editor - Schindler, Hans J.; Türp, Jens Christoph (European journal of orthodontics, 2010)
We write to comment on the article by Kirveskari and Jämsä (2009). Therein, the authors reported that among adult females, who considered their work physically stressful to the cervicobrachial musculature, ‘meticulous occlusal adjustment aimed at elimination of all occlusal interferences’ (p. 491) at the initiation of the investigation and during annual follow-ups decreased later demand for therapy of symptoms located in the head, face and/or cervicobrachial regions. These findings complement results from an earlier randomized controlled trial in which it was shown that regular biannual occlusal adjustment over a period of 4 years among healthy children and adolescents led to a statistically significant reduction of the incidence of symptoms and signs of temporomandibular disorders (TMD) (Kirveskari et al., 1998).